The Status of Women and Sexual Equality in the Sunnah | مكانة المرأة والمساواة الجنسية في السنة النبوية - Rizqa Ahmadi; Sarikh Khalid (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article talks about woman and gender equality on Islam. This article try to comparesome view of this issue. This article also talks about the history of position of womanfrom past time to time being. Islam appreciate of women and their role in every aspect ofthis life. Islam does not forbid women to work like men. This article will show someprophet tradition on this issue. This article will analise some prophet tradition historicalyand contextualy view from some scholar muslim. This article reject some view fromorientalism that Islam is the religion that does’t respect women and does’t give someattention on gender equality.